Improved modulation schemes for indirect Z-source matrix converter with sinusoidal input and output waveforms - Liu, Xiong (2013)
Z-source energy conversion is a recent concept introduced for adding voltage-boost functionality to the traditional buck-only dc-ac inverter. The same concept can equally be extended to the indirect ac-ac matrix converter, where only a single Z-source impedance network needs to be inserted to its intermediate dc link. The topology formed is, thus, quite straightforward. Its modulation is, however, nontrivial if advantages like buck-boost flexibility, minimum commutation count, ease of implementation, and sinusoidal input and output quantities are to be attained simultaneously. This capability is now pursued through unveiling related modulation theories, so as to better present the indirect Z-source matrix converter as an attractive alternative for ac-ac buck-boost energy conversion. Findings presented have already been verified in simulation and experiment.